1986
DOI: 10.1080/01688638608405173
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychology of multiple sclerosis: A critical review

Abstract: Multiple sclerosis (MS) is a relatively common, chronic progressive neurological illness affecting individuals primarily in the third and fourth decades of life. Autopsy studies indicate that the disease preferentially attacks white matter throughout the CNS, including the cerebral hemispheres. This article reviews the current state of knowledge regarding cognitive dysfunction in MS and relates these findings to neuropathological changes. The view that affective disturbance may also result from cerebral demyel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
1
18

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(185 citation statements)
references
References 110 publications
(108 reference statements)
3
163
1
18
Order By: Relevance
“…[48][49][50] Those with decreased cognitive functioning are likely to experience difficulties in the areas of retrieval, psychomotor speed, and complex attention. 51 Given that perceived cognitive disability was found to be a significant predictor of less successful adjustment to MS, patients' cognitive complaints should be respectfully addressed and objectively assessed.…”
Section: Resultsmentioning
confidence: 99%
“…[48][49][50] Those with decreased cognitive functioning are likely to experience difficulties in the areas of retrieval, psychomotor speed, and complex attention. 51 Given that perceived cognitive disability was found to be a significant predictor of less successful adjustment to MS, patients' cognitive complaints should be respectfully addressed and objectively assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Des analyses post-mortem ont permis de constater que 90 % des individus diagnostiqués de SEP présentent des plaques cérébrales alors que des scans cérébraux permettent d'observer que 41 % montrent une dilatation ventriculaire, signe d'atrophie corticale (Rao, 1986). L'imagerie cérébrale ne permet pas encore d'établir de corrélation exacte entre la localisation des plaques ou leur étendue et les manifestations neuropsychologiques telles que mesurées par des tests (Penner, Opwis, & Kappos, 2007).…”
Section: La Sclérose En Plaquesunclassified
“…Substantial deficits are found in both working memory, the processing of short lived, 'on-line' information, and long term memory, an unlimited permanent memory store [41]. Other research has found that long term memory deficits may be a result of a specific weakness in retrieval as opposed to encoding or storage [42]. Metaanalysis [43] [43].…”
Section: Vitamin D As An Agent For Cognitive Enhancementmentioning
confidence: 99%